A limit is a mathematical computation that tells us the value assumed by a mathematical expression/function as the independent variable approaches a certain value.

Let a function `f(x`) be defined in an open interval in the neighborhood of the number "a".

If as `x` approaches "a" from both left and right sides of "a", `f(x`)approaches a specific number "L" then "L" is called the limit of `f(x)` as `x` approaches
a.

**Symbolically**,

Limit is expressed as follows:

`Lim_(x->a) f(x) = L `

And is read as "Limit of `f(x)` as `x-> `a is L" .

Under this definition of the limit of a function, we can categorize limits into these three types:

- Limit of a function as X approaches some fixed constant
- Limit of a function as X approaches +ve/-ve infinity
- Limit of a function as X approaches 0

There are some fundamental theorems on Limits of functions. We present their brief statements here.

`Lim_(x->a) [u(x) + v(x)] `= `Lim_(x->a) u(x) `+ `Lim_(x->a) v(x) `= P + Q

`Lim_(x->4) (x + 6)` = `Lim_(x->4) x` + `Lim_(x->4) 6` = 4 + 6 = 10

`Lim_(x->a) [u(x) – v(x)] `= `Lim_(x->a) u(x)` – `Lim_(x->a) v(x) `= P – Q

`Lim_(x->4) (x – 6)` = `Lim_(x->4) X` – `Lim_(x->4) 6` = 4 – 6 = –2

`Lim_(x->a) [Cu(x)]` = C `Lim_(x->a) [u(x)]` = CP

` Lim_(x->3)(2x) = 2 Lim_(x->3)(x) = 2 (3) = 6 `

`Lim_(x->a) [u(x) v(x)] `= `[Lim_(x->a) u(x)] [ Lim_(x->a) v(x)]` = P Q

`Lim_(x->3)(2x)(x – 1)` = `[Lim_(x->3)(2x)][Lim_(x->3)(x – 1)] `= `[2(3)][3 – 1] `

= (6)(2) = 12

= (6)(2) = 12

`Lim_(x->a) (( u(x) )/( v(x)))` = ` ( Lim_(x->a) u(x) )/(Lim_(x->a) v(x))`= ` ( P )/( Q )(`Provided `Q ≠ 0)`

`Lim_(x->1) (( 2x+1 )/( x+2)) = ((Lim_(x->1) (2x+1) )/(Lim_(x->1) (x+2)))` = `( 2(1)+1 )/( 1+2)`= ` ( 3 )/( 3)= 1 `

`Lim_ (x->a) [ u(x)] ^n = (Lim_(x->a) [ u(x)] )^n = P^n `

`Lim_(x->4)` `(3x – 9)^4` = `(Lim_(x->4) (3x – 9) )^ 4` = `(3(4) – 9) ^4` = ` (3) ^4 = 81`

In Calculus, many a times there comes a situation where putting the value of `x` gives us an expression of the form `( 0 )/( 0 )` .When such a situation arises, we use simplification method to factorize both the numerator and denominator expressions to see if there is a factor common to both. If such a common factor does occur, we cancel them about and are usually left with an expression in which putting the limit does not give us ` ( 0 )/( 0 ) ` form. We have presented some of the examples of such a scenario here:

`Lim_(x->1) ( x^2 - 1 )/(x^2- x )`= `((1)^2 - 1 )/((1)^2- 1 )`= ` ( 0 )/( 0 ) `

Hence we try to factorize the terms.

` Lim_(x->1) ( x^2 - 1 )/(x^2- x )= Lim_(x->1) ((x –1)(x+1) )/(x( x-1) )= Lim_(x->1)( (x+1) )/(x ) = ( (1+1) )/1 = 2 `

In evaluating limits at infinity, we divide both the numerator and the denominator terms by the highest power of variable that appears in the denominator and then put the limit in the new formed expression.

We first divide both the numerator and the denominator by the highest power of x in the denominator which is 3.

`Lim_(x-> 8)((3x)^2/( x)^3 – ( 2x)/( x)^3 )/(( 4x)^3/( x)^3 - ( 2x)^2/( x)^3 + ( 2)/( x)^3 )=Lim_(x-> 8)(( 3)/( x ) – ( 2)/( x)^2 )/( 4 – ( 2 )/( x ) + ( 2)/( x)^3 )`

Putting the limit value of X = 8

` Lim_(x-> 8)(3x^2 – 2x )/( 4x^3- 2x^2+ 2 ) = (0 – 0 )/( 4 – 0 + 0 )= 0`

If ` theta ` is measured in radians, then `Lim_(T -> 0)( sin T)/T=1`

This is an important Mathematical result and will be used in many examples that you will come across in the subject of Limits and Calculus.
We are not including the proof of this identity here as it might be out of your scope. We will focus more on understanding the solution
strategies.

We solve a few examples that make use of this identity.

We are supposed to evaluate the

`Lim_(T -> 0)( sin 4T)/T`
Putting ` x = 4T =>T= `x / 4

` Lim_(T -> 0) ( sin 4T)/T ` = `Lim_(x -> 0) ( sin x )/(x/4) ` `(->x -> 0 ` as` T -> 0)`

= 4 `Lim_(x -> 0) ( sin x )/x`

= 4 (1) = 4 ` (∵ Lim_(x -> 0)( sin x )/x = 1)`

` Lim_(T -> 0) ( sin 4T)/T ` = `Lim_(x -> 0) ( sin x )/(x/4) ` `(->x -> 0 ` as` T -> 0)`

= 4 `Lim_(x -> 0) ( sin x )/x`

= 4 (1) = 4 ` (∵ Lim_(x -> 0)( sin x )/x = 1)`

If we directly put the value of limit x into the expression, we get a `( 0 )/( 0 ` form. If however we simplify the numerator term, it becomes easy to evaluate the limit as shown below.

`Lim_(x -> -1)( x^3 - x)/(x + 1 ) ` = `Lim_(x -> -1) ( x(x^2 – 1) )/(x + 1 )`= ` Lim_(x -> -1) (x(x – 1)(x +1))/(x + 1 )`

= `Lim_(x -> -1) x(x-1)` = (–1) (–1 – 1) = 2

= `Lim_(x -> -1) x(x-1)` = (–1) (–1 – 1) = 2

© 2023 iPracticeMath | All Rights Reserved | Terms of Use.